Axial crush behavior and energy absorption capability of foam-filled GFRP tubes under elevated and high temperatures. (1st August 2016) - Wang, Lu; Fan, Xueming; Chen, Hao; Liu, Weiqing
Abstract: Foam-filled circular composite tube has been widely used in safety design of automobile, space craft recovery and so on due to its advantage of high energy absorption, light weight and anti-corrosion. But the axial crush behavior and energy absorption capability of foam-filled composite tubes are threatened by elevated and high temperatures. In practice, the effects of high temperatures cannot be ignored because composites and foam are sensitive to temperature. In this paper, an experimental investigation was carried out to evaluate the effectiveness of energy absorption of foam-filled circular glass fiber reinforced plastic (GFRP) tube under elevated and high temperatures. The temperature range was from 20 °C to 110 °C, covered the glass transition temperature (92 °C). In the meantime, the effects of high environmental temperatures on failure mode, crush force efficiency, energy ductility coefficient and specific energy absorption were also studied. The test results demonstrated that the axial crush behavior and energy absorption capacity of foam-filled GFRP tubes were determined by the environmental temperature. The foam-filled GFRP tubes can achieve top crashworthiness performance when the environmental temperature was less than 70 °C.